Role of interleukin-1 and tumour necrosis factor in leukocyte recruitment to acute dermal inflammation - Andrew C. Issekutz; Nancy Lopes; Thomas B. Issekutz (Hindawi Limited, 1992)
The cytokines IL-1 and TNF-α are involved in inflammation and their production is stimulated by various agents, especially endotoxin (LPS). Here, using the human IL-1 receptor antagonist (IL-1RA) and a new monoclonal antibody (mAb 7F11) to rabbit TNF, the role of endogenous IL-l and TNF production in acute (3h) leukocyte (PMNL) recruitment to dermal inflammation in rabbits has been studied. IL-1RA inhibited by 27% the PMNL accumulation in reactions induced by killed Escherichia coli (p < 0.05) but not by LPS. The monoclonal antibody to TNF inhibited by 27% and 38% (p < 0.002) the PMNL accumulation in LPS and E. coli reactions respectively, but a combination of the mAb with IL-1RA was not more effective. Treatment of human umbilical vein endothelium with LPS for 3 h activated endothelium to induce PMNL transendothelial migration in vitro, which was not inhibited by IL-1RA, antibody to TNF-α, IL-1 or to IL-8. In conclusion, TNF and IL-1 may partially mediate acute PMNL infiltration in vivo to LPS and Gram negative bacteria, but there is a major IL-1/TNF independent mechanism, at least in dermal inflammation, which may be due to direct LPS activation of the microvasculature or perhaps the generation of cytokines other than IL-1 and TNF.